Studi Lingkungan Pengendapan dan Diagenesis Batuan Berdasarkan Analisis Petrografi di Daerah Sukolilo, Pati, Jawa-Tengah - Kalimi; Wahyu Budi Kusuma (Jurnal Nasional Pengelolaan Energi MigasZoom, 2019)
Sandstones of Ngrayong Formation are an important reservoir in the north-east Java basin while the Bulu Formation generally functions as an aquifer in the study area. The quality of aquifers and reservoirs in the form of porosity and permeability can be influenced by the diagenesis process. This study aims to determine the depositional environment and diagenesis processes that occur in rocks of Ngrayong Formation and Bulu Formation. Sandstones as sedimentary rocks generally undergo diagenetic processes consisting of compaction, cementation, and dissolution, while carbonate rocks diagenesis processes are very varied but the most important is the process of dissolving and fracturing as forming porosity. From the results of the petrographic analysis, it can be seen that the depositional environment of the Ngrayong Formation is inner-neritic to middle-neritic while the Bulu Formation is deposited in the inner shelf environment. The diagenesis process that occurs is compaction, cementation, dissolution and micritization.